Challenges and Responses to International Investment Rule-making - Tao, Zihan (International Journal of Social Sciences and Public Administration, 2024)
The world economic pattern is experiencing a great change that has not been seen in a hundred years, and the construction and adjustment of the international investment rules system is an important manifestation of the multipolarity of the world economy, which plays an important role in promoting the healthy development of the investment pattern. However, in the process of development, the international investment treaty rule system is facing many difficulties, such as "fragmentation", too many bilateral investment treaties, intensified conflicts between developed and developing countries, and unsound dispute settlement institutions, etc. In this regard, the establishment of a "de-fragmented" international investment treaty rule system is a major challenge. For this reason, it is important to establish a "de-fragmentation" mechanism, reform the investment dispute settlement bodies and enhance the influence of developing countries, with a view to promoting the liberalisation and facilitation of international investment and improving the international investment treaty rules system.